Thermal characterization of nanoscale material - Ho, Weng Fei. (2009)
This final year project presents the thermal property measurements of several nanoscale thin film materials: multiwalled carbon nanotubes (MWCNT), tetrahedral amorphous carbon (ta-C) and CrAlSiN nanocomposites, using pulsed photothermal reflectance (PPR) technique at room temperature. Thin gold layers were deposited on top of these samples through e-beam deposition process to enhance sample heat absorption during photothermal experiment. Data values obtained from the measurements were used to curve-fit the thermal properties of the samples using three-layer model of transmission line theory of heat conduction. In initial stage, silicon dioxide (SiO2) thin films were used to calibrate the experiment setup. Results showed that the thermal conductivity of SiO2 was ~1.47 W/m K, which was quite close to its bulk value of 1.458 W/m K. With the experiment setup proven to be well calibrated for subsequent sample measurements, the mean effective thermal conductivity of MWCNT, ta-C and CrAlSiN samples are evaluated to be about 1.50, 9.10 and 6.68 W/m K respectively. For thermal diffusivity, the values obtained for these materials were in the range of 10-7, 10-4 and 10-7 m2/s respectively.